SINTESIS DAN KARAKTERISASI WOLLASTONITE BERBASIS PREKUSOR BIOGENIK SILIKA ABU SEKAM PADI - Amilia Rasitiani; Dwi Asmi; Muhammad Badaruddin (Department of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2023)
The aim of this research is to make wollastonite from silica obtained from rice husk ash and commercial calcium carbonate using the solids reaction method. The DTA-TGA results show mass due to the evaporation of H2O and the decomposition of CaCO3 into CaO along with the calcination temperature, in addition, the DTA results also identify the formation of the ?-CaSiO3 phase and the ?-CaSiO3 phase. The XRD results of wollastonite obtained were dominated by the ?-CaSiO3 phase and the minor phase was ?-CaSiO3 this was indicated by the peak intensity of the ?-CaSiO3 phase which was higher than the peak intensity of the ?-CaSiO3 phase. the second phase in wollastonite is also the result of FTIR results through the analysis of the Si-O-Ca functional group in each wollastonite sample. In addition, the results of the SEM analysis showed the shape of the spheroidal particles (spherical) with an average grain size of 0.19 m, 0.35 m and 0.68 m for the calcination temperatures of 900 oC, 1000 oC and 1100 oC, respectively. The results of this study indicate that the manufacture of wollastonite from the basic ingredients of rice husk silica and commercial calcium carbonate has potential as an alternative material for the manufacture of wollastonite.